Preventive Observations: A new approach to reduce workplace accidents - Huachin Mantarí, Elsse Yudith (2023)
The lack of observation has brought side effects in the different sectors and activities that are carried out in different countries. This study is a systematic review of the literature. From a total of 30 published articles, 10 most relevant scientific articles and reports on preventive observation were considered. Some observations were made during the sampling carried out on a group of workers made up of 5 workers, resulting in deviations in different aspects, such as risk behaviors (people), defective equipment, defective materials and substandard areas. This means that in all the approaches there are deviations that are generated by the workers that would lead to the materialization of unwanted events, however, if the observations are detected in time and corrective actions are taken immediately, all accidents are prevented. worked. The observation carried out is preventive when it is observed before an accident occurs, when it is communicated to whom it corresponds and corrective actions are taken to avoid the materialization of an unwanted event. Being one of the challenges in the different sectors the prevention of accidents at work and having to implement a fundamental tool for the prevention of accidents.